Neural Systems Under Change of Scale - Fagerholm, Erik D.; Foulkes, W. M. C.; Gallero-Salas, Yasir; Helmchen, Fritjof; Friston, Karl J.; Leech, Robert; Moran, Rosalyn J. (Frontiers in Computational Neuroscience, 2021)
We derive a theoretical construct that allows for the characterisation of both scalable and scale free systems within the Dynamic Causal Modelling framework. We define a dynamical system to be ‘scalable’ if the same equation of motion continues to apply as the system changes in size. As an example of such a system, we simulate planetary orbits varying in size and show that our proposed methodology can be used to recover Kepler’s third law from the timeseries. In contrast, a ‘scale free’ system is one in which there is no characteristic length scale, meaning that images of such a system are statistically unchanged at different levels of magnification. As an example of such a system, we use calcium imaging collected in murine cortex and show that the dynamical critical exponent, as defined in renormalization group theory, can be estimated in an empirical biological setting. We find that a task-relevant region of the cortex is associated with higher dynamical critical exponents in task vs. spontaneous states and vice versa for a task-irrelevant region.